Mauritius: Reforming the sugar cane industry - Autrey, L.C.J.; Ramasamy, S.; Ng Kee Kwong, K.F. (Technical Centre for Agricultural and Rural Cooperation, 2006)
L.J.C. Autrey, S. Ramasamy and K.F. Ng Kee Kwong describe the achievements in the process of introducing precision farming technologies in Mauritius, and the challenges ahead